Eksistensi Ayu Windy Tenun Ikat Dalam Peningkatan Perekonomian Melalui Komodifikasi Kain Endek: Eksistensi Ayu Windy Tenun Ikat Dalam Peningkatan Perekonomian Melalui Komodifikasi Kain Endek - Ni Luh Nyoman Kebayantini; I Gusti Agung Alit Suryawati (Jurnal Sosiologi Nusantara, 2024)
This research examines the creative industry in the field of endek, namely Ayu Windy Tenun Ikat which developed as one of the fashion businesses as an effort to preserve Balinese culture, namely endek. Creative industries are increasingly intensified for the development of skills, creativity, and talents possessed by individuals in creating welfare and employment. Developments regarding the development of tourism-based industries are carried out to improve the regional economy without neglecting socio-cultural aspects. This research uses qualitative methods with a case study approach to meet the need for a detailed, complete and comprehensive understanding of problems with varied and abundant data acquisition. Based on the results of the research, it was found that aAyu Windy Tenun Ikat is a fashion creative industry using cultural heritage that always implements creativity in every innovation. Ayu Windy Tenun Ikat is able to become an innovative actor, an actor who guards cultural heritage with concrete steps that are able to reverse the dominant discourse, as well as being able to take part in improving the economy and supporting the development of Bali tourism. The spirit of preservation is executed by the social practice of commodification of endek fabrics into various fashion products with a modern touch such as bandos, polo T-Shirts, tablecloths, pillowcases, sandals, and so on. The social practice of commodification of endek cloth in MSMEs Ayu Windy Tenun Ikat starts from the establishment of a woman's social values, the desire to have a business, economic expansion supported by the accumulation of various kinds of capital (social, capital, cultural and symbolic) available in her environment. At the same time, the use of physical and non-physical domains is very important to be carried out in order to expand business names and product sales.